Acute leptin exposure reduces megalin expression and upregulates TGFβ1 in cultured renal proximal tubule cells. (5th February 2015) - Briffa, Jessica F.; Grinfeld, Esther; Mathai, Michael L.; Poronnik, Phillip; McAinch, Andrew J.; Hryciw, Deanne H.
Highlights: Opossum kidney proximal tubule cells express leptin protein endogenously. Acute leptin exposure upregulates AMPK and fibrotic mediator expression. Acute leptin exposure reduces megalin expression and albumin handling. AMPK inhibition restores megalin, fibrotic mediators, and albumin handling. AMPK mediates fibrotic mediator expression and impairs albumin handling. Abstract: Increased leptin concentrations observed in obesity can lead to proteinuria, suggesting that leptin may play a role in obesity-related kidney disease. Obesity reduces activation of AMP-activated protein kinase (AMPK) and increases transforming growth factor-β1 (TGF-β1) expression in the kidney, leading to albuminuria. Thus we investigated if elevated leptin altered AMPK and TGF-β1 signaling in proximal tubule cells (PTCs). In opossum kidney (OK) PTCs Western blot analysis demonstrated that leptin upregulates TGF-β1 secretion (0.50 µg/ml) and phosphorylated AMPKα (at 0.25, and 0.50 µg/ml), and downregulates megalin expression at all concentrations (0.05–0.50 µg/ml). Using the AMPK inhibitor, Compound C, leptin exposure regulated TGF-β1 expression and secretion in PTCs via an AMPK mediated pathway. In addition, elevated leptin exposure (0.50 µg/ml) reduced albumin handling in OK cells independently of megalin expression. This study demonstrates that leptin upregulates TGF-β1, reduces megalin, and reduces albumin handling in PTCs by an AMPK mediated pathway.